Periphyton community Structure in the Seagrass Ecosystem of the Malang Rapat Village coast, Bintan Regency, Kepulauan Riau Province - Harahap, Hasbi Ansyori; Sumiarsih, Eni; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Periphyton is a type of algae that commonly inhabit the surface of immersed objects. A research aims to understand the periphyton community (types and abundance) in the seagrass ecosystem of the Malang Rapat Village has been conducted in May 2015. Samplings were conducted 3 times in 3 stations. In each station there were 3 transeck lines with 5 quadrants (1 m x 1 m) in each line. Periphyton samples were taken by scraping the seagrass surface by tooth brush in the area of 5x2 cm2. Periphyton collected were then preserved in lugol 2-3 drop/40 ml and then was identified.Result shown that there were 33 periphyton species present and they are belonged to 4 classes, namely Bacillariophyceae (28 species), Chlorophyceae (2 species), Cyanophyceae (2 species) and Dinophyceae (1 species). Periphyton abundance was 13,976-29,228 cells/ cm2. In general, the H’ was 3.941-4.252; C was 0.063-0.090 and E was 0.815-0.873. The water quality parameters are as follows: temperature was 30.67-31.34 0C; brightness was 0.27-0.35 m; turbidity was 1.39-1.79 NTU; current speed was 0.11-0.12 m/s; depth was 0.27-0.35 m; pH was 8; DO was 7.60-7.96 mg/L; free CO2 was 4.3-4.8 mg/L; salinity was 30.4-30.67 ‰; nitrate was 0.026-0.031 mg/L and phosphate was 0.048-0.123 mg/L. Based on periphyton community, it can be concluded that the aquatic environment in the waters of Trikora Beach, Malang Rapat Village is balance.Keyword : Periphyton, Seagrass Ecosystem, Malang Rapat Village